Providers and patients face-to-face: what is the time? - Andrew D. Racine (BMC, 2017)
Abstract Background The frequency of visiting primary care providers and the duration of those visits varies substantially by patient demographics and across different developed countries. The significance of a cumulative measure of this time spent with providers in face-to-face visits is not well understood. Commentary In a recent IJHPR issue Nathan and co-authors have suggested a new metric for capturing the cumulative time spent annually in face-to-face encounters between providers and patients. The annual accumulated duration of time (AADC) of visits was constructed using a 2% random sample of adult patients from the Clalit health plan in Israel for the year 2012. The authors calculated the mean AADC to be 65.7 min with average visit durations of 7.6 min. A presumption underlying this analysis is that the metric captures the magnitude of activity devoted to eliciting relevant clinical information, synthesizing the significance of those data, and communicating the importance of that thinking to patients so that they might make informed decisions regarding their health care. But measuring the time spent with a provider is but a surrogate marker of these activities and the lack of correlation between time spent with providers and health outcomes suggests that as a surrogate it may not be that robust a measure. It is possible that what is being captured through this metric is the influence of economic incentives faced by individual practitioners and the structure of health care financing in different societies rather than a portrait either of clinical complexity or quality of care. Conclusions The advent of this new measure of cumulative provider time with patients signals the importance of accurate measurement as a vital first step in understanding the meaning of data but reminds us of an obligation to inquire beyond the measurements themselves to arrive at appropriate policy-relevant conclusions.